Bipolarization in ten Sub-Saharan African countries - (:unkn) unknown (My University, 2023)
A new and flexible bipolarization index shows that consumption bipolarization within ten SSA countries is low compared to inequality. Sectoral and regional income disparities drive observed bipolarization; religions and ethnic groups have limited contributions.
Keywords: African Research